Program Pelatihan Sistem Electronic Fuel Injection (EFI) Bagi Siswa SMK N 2 Payakumbuh - Putra, Randi Purnama; Wagino, Wagino; Amin, Bahrul; Afnison, Wanda (Universitas Negeri Padang, 2021)
One of the mandatory criteria for SMK graduates is to have a competency renewal value. Competence values that lack novelty will be unable to compete in the current era of rapid technological development. The school has a big role in designing learning that has new value. To achieve this, the school must move quickly to present collaborative programs, training with other agencies that do have professionalism in their fields.The problems experienced by Vocational High Schools above are one of the responsibilities of lecturers as educators, wherefrom the threefold missions of Higher Education that must be implemented there are points of community service. The lecturer profession is obliged to do community service related to the problems that arise around it. Based on the problems experienced by Vocational Schools at the initial point, our community service team from the Automotive Engineering Department through LP2M UNP tried to cooperate with schools in presenting new competencies. This activity is in the form of Electronic Fuel Injection (EFI) fuel system training for students of SMK N 2 Payakumbuh.From the evaluation results, it was found that students' understanding of the fuel injection system (EFI) material increased with an average increase in understanding of 12-18%. The author believes that if this is continued consistently, it can have an impact on improving the quality of PBM in SMK N 2 Payakumbuh.